ICT Enabled Learning: A tool in Crisis Management - Khanna, Shallu (Pandawan, 2020)
Due to Covid -19 Pandemic educational institutions have closed in 107 countries affecting more than 860 million students. Information and communications technology have been widely adopted in most educational institutions in order to support e-learning through different learning methodologies. Information and communication technologies have changed the face of managing information in crisis, warning, impact and response. Information and communication technologies are changing the way that users are responding to environmental and health disruptions. In conflict zones it is dangerous for people to travel and maintain normal activities. However with mobile phones and internet applications and data on cloud, people can coordinate and communicate to help restore activities through negotiating travel, increasing situational awareness and conducting online social interaction. Security and compliances have become the key and mandatory for the organisation as data is growing in exponential form. Privacy laws applies not only to government operations but also to private enterprises and commercial transactions to understand how user data is being handled, processes to customer and visitor. It exploits to keep certain data confidential and if exposed it has to be with consent of user. Crisis management is designed to protect an organization and its stakeholders from threats and/or reduce the impact felt by threats. All the stages has discussed in detail along with diagram keeping concern in a crisis has to be public safety. A failure to address public safety intensifies the damage from a crisis. Reputation and financial concerns are considered after public safety has been remedied.